Muddling towards cooperation: a CIFOR case study of shared learning in Malinau district, Indonesia - Wollenberg, Eva Karoline; Iwan, R.; Limberg, G.; Moeliono, M.; Rhee, S.; Sudana, M. (2004)
This paper describes the experience of CIFOR research team in facilitating local communities to manage their natural resources in Malinau District, East Kalimantan, Indonesia during the Otonomi Daerah reform period (1998-present). The case examines how the CIFOR team used informal, shared learning to support more socially just decision among groups that shared and often contested claims to forest resources and responsibility for their management. This paper reports on the outcomes, challenges and lessons of this experience. The team experience leads them to question the desirability of creating formalised multistakeholder learning mechanisms and common strategies on single platforms, and instead, to stress the value of informal, embedded approach focused on incremental strengthening of communities is especially helpful during times of uncertainty where rapid adaptation to changing circumtances is necessary.